Exploring the black box : technology, economics, and history - Rosenberg, Nathan, 1927-2015 (Cambridge University Press, 1994)
The process of technological change takes a wide variety of forms. Propositions that may be accurate when referring to the pharmaceutical industry may be totally inappropriate when applied to the aircraft industry or to computers or forest products. The central theme of Nathan Rosenberg's new book is the idea that technological changes are often 'path dependent', in the sense that their form and direction tend to be influenced strongly by the particular sequence of earlier events out of which a new technology has emerged. The book advances the understanding of technological change by explictly recognising its essential diversity and path-dependent nature. Individual chapters explore the particular features of new technologies in different historical and sectoral contexts. This book presents a unique account of how technological change is generated and the processes by which improved technologies are introduced.